Asthma. Issue 10122 (24th February 2018) - Papi, Alberto; Brightling, Christopher; Pedersen, Søren E; Reddel, Helen K
Summary: Asthma—one of the most common chronic, non-communicable diseases in children and adults—is characterised by variable respiratory symptoms and variable airflow limitation. Asthma is a consequence of complex gene–environment interactions, with heterogeneity in clinical presentation and the type and intensity of airway inflammation and remodelling. The goal of asthma treatment is to achieve good asthma control—ie, to minimise symptom burden and risk of exacerbations. Anti-inflammatory and bronchodilator treatments are the mainstay of asthma therapy and are used in a stepwise approach. Pharmacological treatment is based on a cycle of assessment and re-evaluation of symptom control, risk factors, comorbidities, side-effects, and patient satisfaction by means of shared decisions. Asthma is classed as severe when requiring high-intensity treatment to keep it under control, or if it remains uncontrolled despite treatment. New biological therapies for treatment of severe asthma, together with developments in biomarkers, present opportunities for phenotype-specific interventions and realisation of more personalised treatment. In this Seminar, we provide a clinically focused overview of asthma, including epidemiology, pathophysiology, clinical diagnosis, asthma phenotypes, severe asthma, acute exacerbations, and clinical management of disease in adults and children older than 5 years. Emerging therapies, controversies, and uncertainties in asthma management are also discussed.